2011
DOI: 10.1371/journal.pone.0025320
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Therapy during the Peri-Infarct Period Attenuates Left Ventricular Dysfunction and Remodeling after Myocardial Infarction

Abstract: Although statins impart a number of cardiovascular benefits, whether statin therapy during the peri-infarct period improves subsequent myocardial structure and function remains unclear. Thus, we evaluated the effects of atorvastatin on cardiac function, remodeling, fibrosis, and apoptosis after myocardial infarction (MI). Two groups of rats were subjected to permanent coronary occlusion. Group II (n = 14) received oral atorvastatin (10 mg/kg/d) daily for 3 wk before and 4 wk after MI, while group I (n = 12) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 45 publications
3
16
0
Order By: Relevance
“…Collagen types I and III (COL I and COL III, respectively) are the most abundant collagen types in cardiac tissue, together accounting for 95% of the total collagen [2, 7, 8]. Ventricular remodeling is unfavorable to the myocardium in part because it is associated with accumulation of collagen and other ECM components [9]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen types I and III (COL I and COL III, respectively) are the most abundant collagen types in cardiac tissue, together accounting for 95% of the total collagen [2, 7, 8]. Ventricular remodeling is unfavorable to the myocardium in part because it is associated with accumulation of collagen and other ECM components [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Statins stabilize atherosclerotic plaques in cardiovascular disease. Their pleiotropic effects include antioxidant and anti-inflammatory activities, improvement of endothelial function, and reduction of cytokine expression [9, 21, 22]. Atorvastatin has shown beneficial effects in the inhibition of cardiac fibroblasts in vitro , the reduction of fibrosis, and the expressions of COL I and COL III [21, 23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…Although lipid lowering effects account for a significant part of statin-mediated protection, additional benefit may be afforded by anti-inflammatory effects, by modulation of the coagulation and fibrinolytic systems, by direct protection of ischemic cardiomyocytes, or by actions on endothelial cell behavior (185). In experimental models of myocardial infarction, statins reduced adverse remodeling without affecting the size of the infarct (359); the clinical significance of these observations remains unclear. The protective effects of statins on the remodeling infarcted heart may be mediated through antifibrotic effects (55,359) suppression of MMP expression (154,271), through activation of the angiogenic response (213), or through attenuation of inflammation (229).…”
Section: Statinsmentioning
confidence: 99%
“…In experimental models of myocardial infarction, statins reduced adverse remodeling without affecting the size of the infarct (359); the clinical significance of these observations remains unclear. The protective effects of statins on the remodeling infarcted heart may be mediated through antifibrotic effects (55,359) suppression of MMP expression (154,271), through activation of the angiogenic response (213), or through attenuation of inflammation (229). Experimental studies showed that statin-mediated protection in the infarcted and remodeling myocardium requires endothelial nitric oxide availability (213,266).…”
Section: Statinsmentioning
confidence: 99%
“…In recent years, many studies further validated its anti-apoptotic effect in animal models of myocardial ischemia and reperfusion injury [27], coronary atherosclerosis [28], myocardial infarction [29], and renal ischemia-reperfusion injury [30]. More and more studies show that atorvastatin may regulate PTEN/PI3K/Akt cell signaling pathways, although statins may have different regulatory effects in different pathological conditions.…”
Section: Figmentioning
confidence: 99%